2013
DOI: 10.1007/s00431-013-2194-1
|View full text |Cite
|
Sign up to set email alerts
|

High-dose gentamicin in newborn infants: is it safe?

Abstract: Dosing regimens often recommend lower gentamicin doses in neonates (3-5 mg/kg) than in older children (7 mg/kg or more) despite the higher volume of distribution in neonates. We studied an extended-interval high-dose (6 mg/kg) gentamicin regimen in a single tertiary neonatal unit from 2004-2012. During the first week of life, dosing interval was 24 h for term infants, 36 h for preterm infants with gestational age (GA) 29-36 weeks and 48 h for preterm infants with GA <29 weeks. After the first week of life, dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
1
25
0
2
Order By: Relevance
“…The difference in the doses of aminoglycosides in term infants is explained by different local guideline recommendations at the hospitals. We did not register any switch of aminoglycoside doses in term infants during the same course, and one study showed that aminoglycosides safely can be dosed 6 mg/kg every 24 h in term born infants (22). The higher number (mean) of daily administrations with ampicillin at the DH may be explained by the recommendation in a commonly used local Norwegian neonatal supervisor to increase the number of administrations from two up to four per day in severe infections/meningitis (23).…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the doses of aminoglycosides in term infants is explained by different local guideline recommendations at the hospitals. We did not register any switch of aminoglycoside doses in term infants during the same course, and one study showed that aminoglycosides safely can be dosed 6 mg/kg every 24 h in term born infants (22). The higher number (mean) of daily administrations with ampicillin at the DH may be explained by the recommendation in a commonly used local Norwegian neonatal supervisor to increase the number of administrations from two up to four per day in severe infections/meningitis (23).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged or repeated concentrations above a certain value (6×MIC is one estimate) are also usually deprecated. However it has been argued that a single high peak which decays rapidly may perhaps not be too dangerous, due to saturation effects in drug uptake for both ear and kidney (4,25,36). Comparing with Tables I and II indicates that the high initial doses needed to achieve high predicted values of E F , especially doses of 6 mg/kg or more which are used only rarely for neonates (36), are as yet neither unambiguously safe nor unambiguously ruled out by toxicity constraints.…”
Section: Regimens With Large First Dose But Small Total Dose: Toxicitymentioning
confidence: 95%
“…Clinical guidelines for neonates vary (4,25,30,31,35,36). Guidelines often specify that free drug concentration in the central compartment should include frequent or prolonged troughs<MIC (=2 mg/L) during the first week, which our extreme examples (e.g.…”
Section: Regimens With Large First Dose But Small Total Dose: Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Непрохождение скринингового аудиологического теста у недоношенных детей, принимавших ототоксические антибиотики, по данным различных авторов, колеблется от 8 до 22% [3,4]. Значительный разброс в результатах может быть связан как с разницей в выборках, сроках первичного аудиологического обследования, принятых в различных стационарах мира, так и с использованием различных антибактериальных препаратов.…”
unclassified